PROPERTIES OF LEXICAL NETWORKS BUILT ON NATURAL AND RANDOM TEXTS - Oleh Kushnir; A. Drebot; D. Ostrikov; O. Kravchuk (Електроніка та інформаційні технології, 2024)
We study experimentally and analyze phenomenologically the properties of lexical co-occurrence networks. Our linguistic networks are built on a natural text (NT) and a random text (RT), which has been obtained after randomizing the NT on the lexical level. Another subject of our interest is a random-graph-type (RG) network having the same number of nodes as in the NT network and randomized links among those nodes. We consider non-weighted non-restricted networks where words are not filtered by their frequency and stop words are not removed.